Experimental study on bond performance of GFRP bars in self-compacting steel fiber reinforced concrete - Mazaheripour, H. (2013)
Reinforcing bars made of Glass-Fiber-Reinforced Polymers (GFRP) are more and more common as internal reinforcement of concrete structures and infrastructures. Since the design of GFRP reinforced concrete members is often controlled by serviceability limit state criteria (i.e., deflection or crack width control), an accurate knowledge of the GFRP-concrete bond behavior is needed to formulate sound design equations. Furthermore, bond laws currently available and widely accepted for conventional steel rebars cannot be straightforwardly applied for GFRP ones. Hence, an experimental program consisting of 36 pullout bending tests was carried out to evaluate the bond performance between GFRP bars and steel fiber reinforced self-compacting concrete (SFRSCC) by analyzing the influence of the following parameters: GFRP bar diameter, surface characteristics of the GFRP bars, bond length, and SFRSCC cover thickness. Based on the results obtained in this study, pullout failure was occurred for almost all the specimens. SFRSCC cover thickness and bond length plaid important role on the ultimate value of bond stress of GFRP bars. Moreover, the GFRP bars with ribbed and sand-coated surface treatment showed different interfacial bond behaviors.